Synthesis and biological evaluation of quinoxaline derivatives as tubulin polymerization inhibitors that elevate intracellular ROS and triggers apoptosis via mitochondrial pathway. (11th January 2019) - Qi, Jianguo; Huang, Jing; Zhou, Xiaomin; Luo, Wen; Xie, Jiaxin; Niu, Linqiang; Yan, Zhijie; Luo, Yang; Men, Yuhui; Chen, Yanan; Zhang, Yahong; Wang, Jianhong
Abstract: A series of novel quinoxaline derivatives were synthesized and evaluated for their antiproliferative activity in three human cancer cell lines. Compound12 exhibited the most potent antiproliferative activity with IC50 in the range of 0.19–0.51 μM. The compound inhibited tubulin polymerization and disrupted the microtubule network, leading to G2/M phase arrest. Furthermore, compound12 induced ROS production and malfunction of mitochondrial membrane potential. Compound12 led to cancer cells apoptosis in a dose‐dependent manner. Western blot analysis showed that compound12 induced up‐regulation of p21 and affected the expression of cell cycle‐related proteins. The binding mode was also probed by molecular docking. Abstract : A series of novel quinoxaline derivatives was evaluated for their cytotoxic activity. Compound12 showed potent antiproliferative activity against three cancer cell lines, and the biological studies showed that it inhibited tubulin polymerization, induced ROS production, and led to cancer cells apoptosis. The binding mode was also probed.